2021
DOI: 10.3390/biom11071048
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Polydatin/Resveratrol in the ACE2:Spike Recognition during COVID-19 Infection. A Focus on Their Potential Mechanism of Action through Computational and Biochemical Assays

Abstract: In the search for new therapeutic strategies to contrast SARS-CoV-2, we here studied the interaction of polydatin (PD) and resveratrol (RESV)—two natural stilbene polyphenols with manifold, well known biological activities—with Spike, the viral protein essential for virus entry into host cells, and ACE2, the angiotensin-converting enzyme present on the surface of multiple cell types (including respiratory epithelial cells) which is the main host receptor for Spike binding. Molecular Docking simulations evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 86 publications
3
26
0
Order By: Relevance
“…The rationale behind this research is even stronger, since the results obtained from the computational analysis studies such as Excalate4CoV ( , accessed on 10 October 2021) and others [ 12 ] reported the active interface between the SARS-CoV-2 and phenolic molecular structure.…”
Section: Introductionmentioning
confidence: 97%
“…The rationale behind this research is even stronger, since the results obtained from the computational analysis studies such as Excalate4CoV ( , accessed on 10 October 2021) and others [ 12 ] reported the active interface between the SARS-CoV-2 and phenolic molecular structure.…”
Section: Introductionmentioning
confidence: 97%
“…With regard to the ACE2–spike interaction that occurs in COVID-19, molecular docking simulations provided evidence that RSV can bind to spike, ACE2, and the ACE2–spike complex with good affinity. Preliminary biochemical assays revealed a significant inhibitory effect of RSV on ACE2-spike binding [ 221 ]. A recent mini-review found that the antiviral efficacy of RSV for a number of viruses, including the coronavirus.…”
Section: Resveratrol and Covid-19mentioning
confidence: 99%
“…Therefore, topical administration through inhaled formulations, such as an aerosol, could allow the administration of sufficiently high concentrations of the compound through the airways, which are the entry route for SARS-CoV-2 [ 224 , 225 ]. RSV/CMglucan formulation may be appropriate for simultaneously volatilizing aerosols to treat patients with lower respiratory tract diseases [ 221 ]. This could potentially suppress viral replication in the early stages of infection, reducing viral spread in the lower respiratory tract, leading to a reduction in the risk of infection transmission.…”
Section: Resveratrol and Covid-19mentioning
confidence: 99%
“…Furthermore, studies proved the higher responsibility of PD in SARS-CoV-2 infection compared to CLD [ 7 ]. PD, a small protein domain of the ACE2 with many functional groups, has a solid affinity to bind with other molecules, including COVID-19 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Perovskites provide a positive surface charge for fabulous behavior in aqueous media [ 12 ]. Perovskites semiconductors, which can be represented as A 3+ B 3+ O 3 [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ], show spectacular properties in different fields of science. The applications include solar cells [ 14 ], portable and wearable electronic devices [ 15 ], nuclear radiation of monitoring [ 16 ], membranes [ 17 ], and recently in medicine such as photo-medicine and bioelectric implants.…”
Section: Introductionmentioning
confidence: 99%